2008
DOI: 10.1002/humu.20941
|View full text |Cite
|
Sign up to set email alerts
|

How much mutant protein is needed to cause a protein aggregate myopathy in vivo? Lessons from an exceptional desminopathy

Abstract: Myofibrillar myopathies are caused by mutations in desmin, αB-crystallin, myotilin, ZASP, and filamin C genes. Since the vast majority of myofibrillar myopathy causing mutations are heterozygous single amino acid substitutions or small in-frame deletions, the pathogenic role of mutant versus wild-type protein cannot be assessed in human skeletal muscle by standard immunodetection techniques. We report on an exceptional desminopathy due to a heterozygous c.735G>C mutation. Immunoblotting detected full-length 53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 11 publications
1
32
0
Order By: Relevance
“…The presence of cytoplamic aggregates is a key feature in human desminopathy and recently it was reported that the aggregates contain both mutant and WT desmin (Clemen et al, 2009). Similarly, the aggregates formed as a result of expressing desmin K190A, although not as prevalent, resembled the aggregates observed in desminopathy muscle biopsies, which contain desmin and other sarcomere-associated proteins (Schroder et al, 2007).…”
Section: Resultsmentioning
confidence: 84%
“…The presence of cytoplamic aggregates is a key feature in human desminopathy and recently it was reported that the aggregates contain both mutant and WT desmin (Clemen et al, 2009). Similarly, the aggregates formed as a result of expressing desmin K190A, although not as prevalent, resembled the aggregates observed in desminopathy muscle biopsies, which contain desmin and other sarcomere-associated proteins (Schroder et al, 2007).…”
Section: Resultsmentioning
confidence: 84%
“…These deletions were observed in one previously reported patient harboring the heterozygous E245D/D214_E245del (c.735G>C) desmin mutation (Fig. 6a, fourth column), who underwent muscle biopsy at the age of 38 years [14], and a second patient with a R350P (c.1049G>C) desmin mutation. Here, it is noteworthy that the R350P patient with the large-scale mtDNA deletions (father; 52 years of age at biopsy; Fig.…”
Section: Resultsmentioning
confidence: 86%
“…In our electron microscopic analysis of skeletal muscle tissue from desminopathy patients, we discovered that in the case of the heterozygous c.735G>C desmin mutation that leads to the expression of two mutant desmin proteins, E245D and D214_E245del [14], areas with a subsarcolemmal accumulation of mitochondria (Fig. 3a, ma) did prominently localize in close association with pathological protein aggregates composed of granulofilamentous material (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations